The influence of PBL and BBL models on the acquisition and improvement of elementary school students' mathematical concept understanding abilities - Cucu Maryam; Dinn Wahyudin (Himpunan Pengembang Kurikulum Indonesia, 2025)
This study explores the impact of using the Problem Based Learning (PBL) and Brain Based Learning (BBL) models on the achievement and development of elementary school students' mathematical concept understanding abilities. The method applied is a quantitative approach with quasi-experimental and descriptive designs. Participants in this study included sixth-grade students from a public elementary school in Bandung, who were divided into two experimental groups: one used the PBL model, and the other applied the BBL model. The measurement tool used in this study is an essay test designed to assess the ability to understand mathematical concepts. The findings of this study indicate that the implementation of both learning methods, namely PBL and BBL, has a significant impact on students' ability to understand mathematical concepts. Although the BBL model shows a more significant improvement tendency than the PBL model, the difference in effects between the two methods in enhancing mathematical understanding is not statistically significant. This research contributes to developing innovative, appropriate, and efficient mathematics learning models for use at the elementary school level. Abstrak Studi ini bertujuan untuk mengeksplorasi dampak penggunaan model pembelajaran Problem Based Learning (PBL) dan Brain Based Learning (BBL) terhadap pencapaian serta perkembangan kemampuan pemahaman konsep Matematika murid di sekolah dasar. Metode yang diterapkan adalah pendekatan kuantitatif dengan rancangan quasi-eksperimen dan deskriptif. Partisipan dalam penelitian ini meliputi peserta didik kelas VI dari sebuah sekolah dasar negeri di Bandung, yang dibagi menjadi dua kelompok eksperimen: satu kelompok menggunakan model PBL dan kelompok lainnya menerapkan model BBL. Alat ukur yang digunakan dalam penelitian ini adalah tes esai yang dirancang untuk menilai kemampuan pemahaman konsep Matematika. Temuan penelitian ini menunjukkan bahwa penerapan kedua metode pembelajaran, yaitu PBL dan BBL, memiliki pengaruh yang signifikan terhadap kemampuan pemahaman konsep Matematika peserta didik. Meskipun model BBL menunjukkan kecenderungan peningkatan yang lebih besar dibandingkan model PBL, perbedaan efek antara kedua metode dalam meningkatkan kemampuan pemahaman Matematika tidak signifikan secara statistik. Penelitian ini memberikan sumbangan terhadap pengembangan model pembelajaran Matematika yang inovatif, sesuai, dan efisien untuk digunakan di tingkat sekolah dasar. Kata Kunci: kemampuan pemahaman; konsep matematis; pembelajaran berbasis masalah; pembelajaran berbasis otak